Diseño de un programa estratégico operativo de adra ecuador como mecanismo de captación de recursos y financiamiento - Chávez Sigcha, Diana Dolores (2014)
The present project has been made to know the companies that can take part with resources on projects focus on the community, also related to the deeds of Company Social Responsibility (CSR), that nowadays companies worldwide are working with to improve as well as the process and activities of them as the help and benefits for the community. By means of this study, were performed pilot tests and quizzes for knowing what could be the acceptation or rejection by the companies in the moment to quiz the availability to create and participate on Project with their resources that allow to raise the life’s social quality on the community. The level of acceptation to participate with ADRA was 97% on the private companies sector, and of 3% on government’s organizations, this means that there are opportunities of creating new projects that beneficiate to the society and the companies that will collaborate in general.